FACTORS RELATED TO WORK ACCIDENTS ON WASTE MANAGEMENT WORKERS (CASE STUDY IN FINAL PROCESSING PLACE : PECUK INDRAMAYU DISTRICT AND GUNUNG SANTRI CIREBON DISTRICT) IN 2020 - mei nurhayati (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2022)
The role of waste management personnel who work every day to overcome the dangers of environmental pollution due to waste, these workers are at risk of work accidents. The aim is to find out the factors related to work accidents in waste management personnel. Using cross sectional and focus group discussion. The total sampling is 33 respondents. Workers who have an accident will be treated with First Aid in Accidents, even the Environmental Service will follow up. Variables related to work accidents are working hours (ρ=0.023), age (ρ=0.005), fatigue (ρ=0.027). Working hours variable with regression coefficient value = 0.061, age variable with regression coefficient value = 0.020. First Aid in Accidents at work still does not meet the requirements, and workers also do not use complete Personal Protective Equipment. Variable hours of work, age, fatigue associated with work accidents. There is no dominant factor associated with work accidents. It is necessary to hold an Occupational Health and Safety program. Keyword: Work Accident Factors, Waste Management Personnel, Final Processing Place.